Management of Class I and Class II Amalgam Restorations with Localized Defects: Five-Year Results - Javier Martin; Eduardo Fernandez; Juan Estay; Valeria V. Gordan; Ivar Andreas Mjör; Gustavo Moncada (International Journal of Dentistry)
Replacement of dental restorations has been the traditional treatment for defective restorations. This five-year prospective clinical trial evaluated amalgam restorations with localized defects that were treated by means of repair or refurbishing. Fifty-two patients (50% female and 50% male, mean age 28.3±18.1 years, range 18–80) with 160 class I and class II defective restorations were included. The study focused on the application of two minimally invasive treatments for localized restoration defects and compared these with no treatment and total replacement as negative and positive controls, respectively. Restorations were assessed by two calibrated examiners according to modified U.S. Public Health Service criteria, including marginal adaptation, anatomic form, secondary caries, and roughness. At five years, recall was examined in 45 patients with 108 restorations (67.5%). The results suggest that repair treatment is as effective as total replacement of restorations with localized defects, reducing biological costs to the patient and providing new tools to the clinician. Refinishing restoration is a useful treatment for localized anatomic form defects.